Pelatihan Desain Menggunakan Aplikasi Canva Kepada Anak-Anak Di Kupang Gunung Jaya, Kota Surabaya, Jawa Timur Untuk Meningkatkan Kreativitas Dan Kemampuan Visual - Mahardini, Friska Adisti; Suharso, Akbar Bayu Kresno; Friska Adisti Mahardini; Mutyara, Dehana; Devina Azzahra Putri; Manuel Yosia Krista Ananda Wicaksono; Citra Amalia Shiva; Shofiya Syidada (Universitas Wijaya Kusuma Surabaya, 2025)
Creativity and visual ability of children are crucial aspects of their development, influencing how they perceive the world around them and express their ideas. Children naturally possess a rich imagination and great curiosity, which can be expressed through various media, including visual arts. With the advancement of digital technology, children are increasingly exposed to various tools and digital platforms that facilitate creative expression. Canva is an intuitive and user-friendly graphic design platform, allowing users to create visual designs quickly and easily without needing in-depth knowledge of graphic design. Introducing children to the Canva application is an effective strategy to develop their creativity from an early age. This inquire about points to recognize the affect of preparing utilizing the Canva application on upgrading the imagination and visual capacity of children. The research method involves observation, implementation of training sessions, and evaluation based on direct feedback from participants. By leveraging the ease of use of Canva, children can learn to create visually appealing and meaningful artworks, thereby expanding their creativity and visual skills.